2019
DOI: 10.1021/acs.cgd.9b00168
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Macrostep Height and Surface Velocity for a Reaction-Limited Crystal Growth Process

Abstract: This work examined the effect of macrostep height on the growth velocity of a vicinal surface during reaction-(interface-) limited crystal growth under non-equilibrium steady state conditions. The Monte Carlo method was employed, based on a restricted solid-onsolid (RSOS) model with point-contacttype step-step attraction (termed the p-RSOS model). Although this is a simple lattice model, the model surface shows a variety of distinctive configurations depending on the temperature and the driving force for cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…The obtained results do not depend on the initial configuration. This is in contrast to the mean-height of a faceted macrostep n , which is known to be sensitive to the history of the surface configuration 63,64 . As seen from Fig.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…The obtained results do not depend on the initial configuration. This is in contrast to the mean-height of a faceted macrostep n , which is known to be sensitive to the history of the surface configuration 63,64 . As seen from Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Here, �µ R (L) is the crossover point from a vicinal surface with (111) faceted macrosteps to a tilted surface with locally merged steps, and �µ (poly) co (L) is the crossover point from single nucleation growth to poly-nucleation growth at the lower edge of a faceted macrostep 63 . In the region �µ (poly) co (L) < �µ < �µ R (L) , the vicinal surface of the p-RSOS model grows in a step-detachment process in the manner of 2D poly-nucleation at the lower edge of a faceted macrostep 63,64 . Figure 2 shows a typical morphology of a vicinal surface in the region �µ (poly) co (L) < �µ < �µ R (L) (see also Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This attraction, which is the microscopic origin of the discontinuous surface tension, is considered to result from quantum interactions between steps at step meeting points [10]. Our non-equilibrium steady-state study [11][12][13] showed that the height of the faceted macrosteps decreases as the degree of non-equilibrium increases.…”
Section: Introductionmentioning
confidence: 79%
“…The RSOS model with point-contact-type step-step attraction (p-RSOS model) partially accounts for the 2nn attractions between atoms. In the p-RSOS model, mono-atomic steps self-assemble to form faceted macrosteps at low temperatures at equilibrium [37][38][39][40][41][42][43][44][45] . In that case, the surface width is different from the results near equilibrium reported in the present paper.…”
Section: Discussionmentioning
confidence: 99%